Individual’s Dominants as Vector of Language Interpretation of Quantity - E. V. Fedyaeva (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The study considers the dominant principle of sense formation in the process of reality perception and conceptualization including the quantitative aspect of being. The individually significant structures of knowledge, i.e. the dominants of the individual’s linguistic consciousness, determine and direct the process of language interpretation. The novelty of the study is seen in the attempt to model the principles of linguistic consciousness in understanding the quantitative properties and relationships. The relevance of the study is determined by the chosen cognitive approach involving the correlation between different mental structures, formats of knowledge and their language representation. The analysis of the empiric material, including the data of English, French, Russian languages, reveals not only the standards of interpretation, i.e. markers of the dominant zones of individual’s linguistic consciousness “exposing” different priority areas, but also identifies cognitive and linguistic mechanisms of meaning configuration. The repertoire of the dominant linguistic consciousness seems to be unique for each individual, because the formation, presence and the degree of certain knowledge structures ‘prominence’ are conditioned by the individual cognitive experience which depends on many factors. The application of the dominant principle allows demonstrating the variability of the cognitive content formatting, the level of linguistic personality development and, as a consequence, the degree of a person’s linguistic creativity.